3D measurement using fringe projection profilometry - M.N. Alkhatib; Y.D. Shmelev; O.A. Tyshova; I.V. Sinilshchikov; A.V. Bobkov (Компьютерная оптика)
This work is devoted to measuring the depth of the 3D object using the structured light method, in particular, phase shift profilometry. Theoretical studies on the methods of three-dimensional measurement systems and fringe projection profilometry are presented. The phase shift profilometry method with an improved calculation of the frequency of sinusoidal patterns is applied. In practical implementation in the environment (20 cm × 30 cm), the algorithm is tested on a stepped object consisting of eight steps with a difference of 150 mm between two successive steps. In this case, the achievable error for measuring such an object is 20 mm. Our method has great potential in industrial applications where the measurement of the smoothing of the surface of the object is needed to find the defect in the surface with high accuracy without contacting the object.